The Engines of Inequality - Maurizio Franzini; Mario Pianta (Intereconomics, 2016)
In Europe and in the United States, one of the legacies of the economic and financial crisis will no doubt be a high and particularly worrying level of economic inequality. Inequality has roots that go well beyond the 2008 collapse, but the stagnation that has followed it has made disparities in income and wealth more serious and more difficult to eradicate. The challenge now is to turn the injustice of current inequality into a theme of public mobilisation and political action.
Keywords: 330; Einkommensverteilung; Vermögensverteilung; Welt